Effect of Packed Red Cells Blood Components on Hemoglobin Levels in Thalassemia Patients in Sleman District Hospital - Reza Suhada (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2022)
Objective. Thalassemia is a genetic disorder that can be experienced by a person. A person suffering from thalassemia can be detected at the age of 2 years. There are two types of thalassemia, namely major and minor. The Sleman district general hospital is one of the referral hospitals for thalassemia patients in the Sleman district. The number of thalassemia patients who were registered and carried out routine examinations were 30 patients. Purpose. This study aims to determine trend changes in hemoglobin levels giving packed red cells in thalassemia patients. Method. This study used descriptive analytic research method by looking at the trend of changes in hemoglobin levels of patients who underwent blood transfusions for 3 months. Results. A total of 30 thalassemia patients were included in this study but there were 3 patients who did not re-control the first post-control during the study. The results of patient data analysis showed that from 30 thalassemia patients, 11 patients had an increasing trend of hemoglobin levels. A total of 4 patients had a trend of decreased hemoglobin levels. A total of 11 patients had a trend of increasing and decreasing hemoglobin levels. And there is 1 patient who has a steady trend of hemoglobin levels. Conclusion. The trend of increasing hemoglobin levels was as many as 11 patients.